(6a+11)=2a+83

Simple and best practice solution for (6a+11)=2a+83 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6a+11)=2a+83 equation:


Simplifying
(6a + 11) = 2a + 83

Reorder the terms:
(11 + 6a) = 2a + 83

Remove parenthesis around (11 + 6a)
11 + 6a = 2a + 83

Reorder the terms:
11 + 6a = 83 + 2a

Solving
11 + 6a = 83 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
11 + 6a + -2a = 83 + 2a + -2a

Combine like terms: 6a + -2a = 4a
11 + 4a = 83 + 2a + -2a

Combine like terms: 2a + -2a = 0
11 + 4a = 83 + 0
11 + 4a = 83

Add '-11' to each side of the equation.
11 + -11 + 4a = 83 + -11

Combine like terms: 11 + -11 = 0
0 + 4a = 83 + -11
4a = 83 + -11

Combine like terms: 83 + -11 = 72
4a = 72

Divide each side by '4'.
a = 18

Simplifying
a = 18

See similar equations:

| x^2+121=2x^2 | | 7d-3d+5d-5-6d=0 | | b-2+3b+64=4 | | -136=8(1+6b) | | 16=2(x-1)-4 | | 4(3x+5)=104 | | 7.50=0.8c+0.5c | | 11=-7p+13+8p | | 6x-50=10-x | | 2m+23=7m-2 | | 0.5c-7.50= | | x^2-3x+24=0 | | 17x^2-22x+6=0 | | -4x+-40-6=-3-6 | | 4+4b=4 | | 7n-18+1=19 | | 8.2(s+4)=6.7x+5.2 | | b-2+3b+6=4 | | 6p-1=p+20 | | 6(x+8)=7X+3 | | 27*x=1800 | | 6(X+8)=7x-3 | | -6+3X-3Y=0 | | 0=-Y+X-4 | | -3+2X=Y | | 7x+5x+10= | | y+5=-10(X-1) | | 18x^2-47x-56=0 | | 3+(5a+5)=35 | | -1-9x=9x+19 | | 15*x^10=67 | | 7(4b-1)=-3b-2 |

Equations solver categories